Long non-coding RNA PVT1 and cancer - Cui, Ming; You, Lei; Ren, Xiaoxia; Zhao, Wenjing; Liao, Quan; Zhao, Yupei (Biochemical and biophysical research communications, 2016)
Genome-wide sequencing technologies have led to the identification of many non-coding RNAs and revealed an important role for these molecules in cancer. Although there have been many studies on the role of short non-coding RNAs in cancer, much work remains to characterize the functions of long non-coding RNAs. PVT1, a long non-coding RNA encoded by the human PVT1 gene, is located in the well-known cancer-related region 8q24, also known as the 8q24 ‘gene desert.’ PVT1 has three main molecular mechanisms of action: participating in DNA rearrangements, encoding microRNAs, and interacting with MYC. Studies on the association between PVT1 and cancer have shown that PVT1 is a potential oncogene in a variety of cancer types. However, the underlying molecular mechanisms of PVT1 in cancer remain unknown. Further studies of PVT1 will be required to test the utility of this molecule as a target for cancer diagnosis and therapy, and they should also increase our understanding of the role of long non-coding RNAs in tumorigenesis. •PVT1 has three main mechanisms of action in cancer.•PVT1's role in cancer is comprehensively discussed, both in bench and clinical work.•PVT1 is a focus of cancer research and a potential target for diagnosis and therapy.